Microdialysis Monitoring of CSF Parameters in Severe Traumatic Brain Injury Patients: A Novel Approach - Thelin, Eric P.; Nelson, David W.; Ghatan, Per Hamid; Bellander, Bo-Michael (Frontiers in Neurology, 2014)
Background: Neuro-intensive care following traumatic brain injury is focused on preventing secondary insults that may lead to irreversible brain damage. Microdialysis (MD) is used to detect deranged cerebral metabolism. The clinical usefulness of the MD is dependent on the regional localization of the MD catheter. The aim of this study was to analyze a new method of continuous cerebral spinal fluid (CSF) monitoring using the MD technique. The method was validated using conventional laboratory analysis of CSF samples. MD-CSF and regional MD-Brain samples were correlated to patient outcome. Materials and method: A total of 14 patients suffering from severe TBI were analyzed. They were monitored using 1. A MD catheter (CMA64-iView, n=7448 MD samples) located in a CSF-pump connected to the ventricular drain and 2. An intraparenchymal MD catheter (CMA70, n=8358 MD samples). CSF-lactate and CSF-glucose levels were monitored and were compared to MD-CSF samples. MD-CSF and MD-Brain parameters were correlated to favorable (Glasgow Outcome Score extended, GOSe 6-8) and unfavorable (GOSe 1-5) outcome. Results: Levels of glucose and lactate acquired with the CSF-MD technique could be correlated to conventional levels. The median extraction ratio using the CMA64 catheter in CSF was 0.98 and 0.97 for glucose and lactate, respectively. Median MD-CSF (CMA 64) lactate- (p=0.0057) and pyruvate (p=0.0011) levels were significantly lower in the favorable outcome group compared to the unfavorable group. No significant difference in outcome was found using the lactate:pyruvate ratio (LPR), or any of the regional MD-Brain monitoring in our analyzed cohort. Conclusions: This new technique of global MD-CSF monitoring correlates with conventional CSF-levels of glucose and lactate and the extraction ratio for the MD catheter is higher than previously described. Increase in lactate and pyruvate in CSF, without any effect on the LPR, correlates to unfavorable outcome.